Using cooperative learning teams to improve exam scores in the introduction to operations management class. (2018) - Triche, Jason; Flamm, Phillip
The introduction to operations management course is a historically difficult course for students. The novelty of the topics, quantitative rigor and difficult concepts makes this course challenging for students. To combat this problem, we implemented a unique cooperative learning program over two different semesters at an AACSB accredited business school. Although the cooperative learning program was voluntary, 41% of the students participated in the program. Exam scores were measured for students who participated in weekly learning groups versus those students who did not participate. The findings show that students who participated in the weekly cooperative learning groups scored significantly better than non-attended students on all three exam across two semesters. The positive outcomes are numerous including higher pass rates for the course, students learning to work in groups and fewer students visiting office hours during the semester.